Ugandan physician attitudes towards a potential, local trauma fellowship program - Alan Zambeli-Ljepović; Treasure Ibingira; Caroline Stephens; Rachel Koch; Marissa A. Boeck; Doruk Ozgediz; Martha Namugga (BMC Surgery)
Abstract Introduction In low-income countries, clinicians trained through a context-specific trauma surgery fellowship program (TFP) can help reduce injury-related mortality to levels closer to those observed in higher-resource settings. Successful implementation, however, hinges on buy-in from local clinicians. We assessed clinician support for a potential TFP in Uganda, considering perceived need, curricular recommendations, barriers, and motivating factors. Methods After cognitive interviews with experts and questionnaire pilot testing, we cross-sectionally surveyed Ugandan consultants (general surgeons and procedural specialists involved in trauma care) and surgical residents at a tertiary, national referral hospital. Respondent percentages were calculated for multiple-choice answers, and we performed thematic analysis of free-text responses using a primarily inductive approach. Results Among 46 faculty (from 13 specialties) and 42 resident respondents, 86% supported a Ugandan TFP. Respondents recommended incorporating emergency general surgery (66%), critical care (84%), and international rotations (76%) into the curriculum. Severe resource and structural deficiencies (82%) and concern about governmental support for post-training employment and compensation (66%) were leading perceived barriers to TFP implementation. Most faculty felt a TFP would improve patient outcomes (93%), overall trainee education (77%), and clinical efficiency (68%). Free-text responses were consistent with survey themes, indicating acute awareness of current trauma system inadequacies and conviction that a TFP would reduce injury-related mortality. Conclusions Ugandan clinicians who care for injured patients view a TFP as crucial to improving injury-related outcomes, despite known barriers. TFP implementation should incorporate curricular recommendations from this survey and address widespread concerns about financial and infrastructural support from the national government and local institutions.